Layers of Survival: Unveiling Maslow’s Hierarchy of Needs in 10 Minutes 38 Seconds in This Strange World - S.R Aswathy; R. Janatha Kumari (International Journal of Psychosocial Rehabilitation, 2020)
This research uses psychoanalytical theory and makes an attempt to understand and analyze in detail the inevitable and unsurpassable role of human needs in survival. It aptly utilizes the theory of Abraham Maslow and studies his hierarchy of needs in detail. The study put forward the relevance of its application in Shafak’s novel 10 Minutes 38 Seconds in this Strange World through the main character Tequila Leila. In this research, researcher focuses in brief about the types of hierarchical needs and approach in a distinct way that reflect the relevance as well as the significance of the needs as used by the character Leila in the novel. The five-tier model of hierarchy of needs as used by the character to deal with problems in her life are Physiological, Safety, Love/ belonging, Esteem, and Self-actualization needs.Literature and Psychology share common ground as both work on the profound intricacies of human relationship and its complexities. The rich tapestry of human experience when intermingled with creative vigour, it gives rise to a new medium where the intense thoughts, feelings, action and emotions gets new colour in rendition. Literature fosters the diverse and the dynamic nature of human experience and paves way for in depth study of the different psychological conditions and subjective experiences of characters by understanding the therapeutic value of intense emotional experience for the overall well being of individuals. Literary works undoubtedly acts as a mirror to reflect the happenings as well as provide a holistic perspective of the myriad nuances of the multifarious nature of human psyche.In this research, the researcher analyses the novel 10 Minutes 38 seconds in this Strange World from the perspective of Abraham Maslow Hierarchy of Needs. Shafak in her novel, brings out the plight of group of voiceless subalterns with due focus on Tequila Leila, the prostitute who heads the storyline. Born and brought up in an ordinary household, Leila as an infant had a smooth life until the death of her only brother from down’s syndrome. The cold indifference of her father followed by the death of her only brother and the repeated sexual abuse of her uncle, made the life of Leila as a child traumatic. The shocking incidents soon after his abuse such as the decision to seek the hand of her abuser’s son in marriage literally demean her confidence in family. The intensity of pain was unbearable for the child and she decides to flee away from her hometown to the city of dreams- Istanbul. Leila was forcefully thrown in to the field of prostitution and she was made to live in accordance with the crisis. The only way of escape for the protagonist is to seek financial stability from the money that earns from the brothel. In her midlife, she meets four social outcasts and develops a strong bond with them as they all share common ground of social injustices from the society where they live. The novel succumbs with the note of the death of Leila and the varied attempts used by the friends for a proper burial for Leila as she was dumped into Cemetery of companions, a place for the voiceless subalterns. Leila, even though, an absent figure she remains an active role model who had high influence on the lives of her friends. Although the novel had several themes from voicing women’s rights to minority issues, the current research focuses on Maslow’s hierarchy of needs from the perspective of psychological perspective.Literary works are manifestation of human life in totality from the range of character’s emotions, feelings, thoughts and the process of working of human mind. The varied psychological conditions of human life is studied in the creative realm and the resilent measures undertaken by it was highlighted .The prime reason behind the selection of this novel as the chosen material for the study is that, it narrates the life experience of the prostitute called Leila and it offers wide scope for the analysis meted out for the psychological reasons that motivate the behaviour of the protagonist with several limitations and setbacks.Maslow theory of Hierarchy of needs put forward a precise and very well organised, systematic approach to human survival with its five-tier model. It acts as a mirror that captures the reflection of individual progress with the satisfaction of each basic needs that ranges from the most basic and necessary element like physiological to the complex self actualization need. The pyramidical structure with which he categorizes the needs acts as a guide to understand in detail about human behaviour and the element emphasizes the diverse and the dynamic nature of human needs.